Pengaruh Lingkungan Kerja dan Beban Kerja terhadap Kinerja Karyawan pada UMKM Fotocopy Piranha Malang (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to analyze the effect of work environment and workload on employee performance at Piranha Photocopy MSME in Malang City. Human resources are a key element in the operational success of MSMEs, so factors that affect performance need to be studied in depth. The study uses a quantitative approach with a cross-sectional design and involves the entire employee population of 49 respondents through total sampling techniques. Data were collected using a closed questionnaire covering variables of work environment, workload, and employee performance, then analyzed using correlation tests and multiple linear regression using SPSS. The results show that the work environment has a positive and significant effect on employee performance with a regression coefficient of 0.332 (sig. 0.003). Workload also has a positive and significant effect with a regression coefficient of 0.207 (sig. 0.008), although its effect is smaller than that of the work environment. An R value of 0.848 indicates a very strong relationship between the independent variables and employee performance, while an R Square of 0.292 shows that 29.2% of the variation in performance can be explained by the work environment and workload.